2018
DOI: 10.1063/1.5047448
|View full text |Cite
|
Sign up to set email alerts
|

A semianalytical “reverse” approach to link structure and microscopic interactions in two-Yukawa competing fluids

Abstract: We study theoretically a prototype hard-sphere two-Yukawa model with competing interactions, under thermodynamic conditions associated with the formation of clusters. We adopt the analytically solvable random phase approximation and show that this theory predicts reasonably well the structure of the fluid-in comparison with exact Monte Carlo results-within a unique parameterization of the direct correlation function inside the hard core of particles. In particular, the theory follows correctly the development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Excluding the Coulomb limit µ = 0, the mean relative deviation between Eqs. (19,21,23,25) and the IEMHNC approximation result is 0.1% whereas the maximum relative deviation is 3.3% for the 4000 (σ, µ = 0, Γ, κ) combinations studied. Higher deviations are generally observed for large values of κ and low values of Γ/Γ m , see also Ref.…”
Section: B Isomorph-based Integral Theory Approachmentioning
confidence: 84%
See 2 more Smart Citations
“…Excluding the Coulomb limit µ = 0, the mean relative deviation between Eqs. (19,21,23,25) and the IEMHNC approximation result is 0.1% whereas the maximum relative deviation is 3.3% for the 4000 (σ, µ = 0, Γ, κ) combinations studied. Higher deviations are generally observed for large values of κ and low values of Γ/Γ m , see also Ref.…”
Section: B Isomorph-based Integral Theory Approachmentioning
confidence: 84%
“…Combining all the above, the reduced excess internal energy for dense repulsive biYOCP liquids is described by Eqs. (19,21,23,25). Excluding the Coulomb limit µ = 0, the mean relative deviation between Eqs.…”
Section: The Rosenfeld-tarazona Decomposition Of the Internal Energymentioning
confidence: 99%
See 1 more Smart Citation
“…For mathematical convenience, c 2K lr (q) has been calculated analytically with the direct correlation function, c 2K lr (r) −β u 2K (r), extended inside the core 52 . Even if the structure factors determined by RPA are not so accurate than those of simulation or integral equations calculations, it has been proven that RPA is an efficient tool to predict the particularities of the structure factor for systems with competing repulsion and attraction interactions 73 .…”
Section: B Double Kac Potentialmentioning
confidence: 99%
“…For systems with competing interactions in the bulk, a large body of research has been reported. The studies have been done in the framework of computer simulations [24,26,27], including those in combination with machine learning techniques [28], approaches such as Landau-Brazowski theory [29], integral equations [24,25,30], and density functional theory [25,[31][32][33]. Far fewer results exist for systems under confinement.…”
Section: Introductionmentioning
confidence: 99%